Analisis Pengendalian Persediaan Produk Darah Menggunakan Metode Continuous Review System (Sistem-Q) - Seku, Agatha; Utomo, Dutho Suh; Sukmono, Yudi (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Blood is a vital necessity because in the event of a shortage, patients can only obtain blood from fellow humans. Blood available at the Blood Donor Unit, such as packed red cells (PRC) is most often needed for medical treatment, but is also often limited. This is due to the fluctuating supply and demand of blood. Based on the problem, a stochastic model with the continuous review system (CRS) or Q-system method is used. The approach will monitor inventory levels continuously, triggering reordering (r), when the stock reaches a certain threshold. This research applies a stochastic model to forecast demand (q), safety stock (ss), reorder point (r), maximum inventory (S), and total inventory cost (Ot). Before the calculation is done, the demand forecasting method is used, then the calculation with the Q-System. Based on data processing, obtained for each blood type A, B, AB, and O, namely, q values of 47, 48, 40, and 20 blood bags. The value of r is 73, 73, 71, and 17 blood bags. This study applies a stochastic model to estimate demand (q), safety stock (ss), reorder point (r), and maximum inventory (S) 259, 56, 42, 21. And the total inventory cost (Ot) IDR 212,429,215, IDR 238,485,254, IDR 157,422,496, and IDR 59,592,451. Keywords: Blood, Inventory, Demand, Q-System